2021
DOI: 10.3390/antibiotics10040366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Physicians’ Views, Perceptions and Experiences about Broad-Spectrum Antimicrobial Prescribing in a Tertiary Care Hospital Riyadh, Saudi Arabia: A Qualitative Approach

Abstract: Antimicrobial resistance (AMR) is a global public health threat associated with increased mortality, morbidity and costs. Inappropriate antimicrobial prescribing, particularly of broad-spectrums antimicrobials (BSAs), is considered a major factor behind growing AMR. The aim of this study was to explore physician perception and views about BSAs and factors that impact upon their BSAs prescribing decisions. Qualitative semistructured telephone interviews over an eleven-week period were conducted with physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A study monitoring the prescriptions for outpatient parenteral antibiotic therapy found that up to 50% of broad-spectrum prescriptions could have been narrowed [ 10 ]. However, even in instances where narrow-spectrum antibiotics are more justified, physicians still have the tendency to prescribe broad-spectrum antibiotics [ 11 ]. This could be because prescribing practices are often habitual, and decisions may be made using treatments most familiar to the prescriber, prompting the use of all-encompassing broad-spectrum antibiotics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study monitoring the prescriptions for outpatient parenteral antibiotic therapy found that up to 50% of broad-spectrum prescriptions could have been narrowed [ 10 ]. However, even in instances where narrow-spectrum antibiotics are more justified, physicians still have the tendency to prescribe broad-spectrum antibiotics [ 11 ]. This could be because prescribing practices are often habitual, and decisions may be made using treatments most familiar to the prescriber, prompting the use of all-encompassing broad-spectrum antibiotics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%